Treatment for overactive bladder: A meta-analysis of transcutaneous tibial nerve stimulation versus percutaneous tibial nerve stimulation. Issue 20 (21st May 2021) - Yang, Ding-Yuan; Zhao, Liu-Ni; Qiu, Ming-Xing
Abstract: Background: We aim to compare the safety and effectiveness of transcutaneous tibial nerve stimulation (TTNS) versus percutaneous tibial nerve stimulation (PTNS) in treating overactive bladder. Methods: A systematical search on PubMed, Embase, clinicalTrial.gov, and Cochrane Library Central Register of Controlled Trials from January 1, 1999 to November 1, 2020 was performed. The primary outcomes were the changes in a 3-day voiding diary. Quality of life scores were also evaluated. Review Manager 5.3 (Cochrane Collaboration, Oxford, UK) was applied to conduct all statistical analyses. Results: A total of 4 trials (2 randomized controlled trials, 1 retrospective study, and 1 before-after study) with 142 patients were eventually enrolled. Compared with PTNS, TTNS had a similar performance in the voiding frequency in 24 hours (mean difference [MD] = −0.65, 95% confidence interval [CI]: −1.35 to 0.05, P = .07), the number of urgency episodes in 24 hours (MD = 0.13, 95% CI: −0.36 to 0.62, P = .60), the number of incontinence episodes in 24 hours (MD = 0.01, 95% CI: −0.13 to 0.14, P = .93), as well as in the nocturia frequency (MD = −0.14, 95% CI: −0.52 to 0.24, P = .47). Moreover, comparable results were observed regarding HRQL scores ( P = .23) and incontinence quality of life scores ( P = .10) in both groups. The total complication rate in the current study was 2.1% (3/142). No adverse events were identified in the TTNS group. Conclusion: Current data supported that TTNS is as effective as PTNS for the treatment of overactive bladder, moreover, with no reported adverse events. However, the evidence is low-grade and well-designed prospective studies with a large sample size are warranted to verify our findings. Abstract : Supplemental Digital Content is available in the text